2004
DOI: 10.1016/j.neuron.2004.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Or83b Encodes a Broadly Expressed Odorant Receptor Essential for Drosophila Olfaction

Abstract: Fruit flies are attracted by a diversity of odors that signal the presence of food, potential mates, or attractive egg-laying sites. Most Drosophila olfactory neurons express two types of odorant receptor genes: Or83b, a broadly expressed receptor of unknown function, and one or more members of a family of 61 selectively expressed receptors. While the conventional odorant receptors are highly divergent, Or83b is remarkably conserved between insect species. Two models could account for Or83b function: it could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

46
1,271
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 1,175 publications
(1,324 citation statements)
references
References 57 publications
46
1,271
3
4
Order By: Relevance
“…To remove tactile cues, we separated males from rivals by using porous netting. To test olfactory cues, we used focal mutant males lacking Orco (formally Or83b , a coreceptor necessary for odorant perception in toto [Larsson et al., 2004]) or wild‐type focal males from which we had removed the third segment of the antennae, which contains sensillae bearing the odorant receptors required for males to respond to the odors of other flies (van der Goes van Naters & Carlson, 2007). Finally, we tested whether D. melanogaster males could be tricked into responding to males of all the heterospecific species equally, following exposure to false olfactory cues.…”
Section: Methodsmentioning
confidence: 99%
“…To remove tactile cues, we separated males from rivals by using porous netting. To test olfactory cues, we used focal mutant males lacking Orco (formally Or83b , a coreceptor necessary for odorant perception in toto [Larsson et al., 2004]) or wild‐type focal males from which we had removed the third segment of the antennae, which contains sensillae bearing the odorant receptors required for males to respond to the odors of other flies (van der Goes van Naters & Carlson, 2007). Finally, we tested whether D. melanogaster males could be tricked into responding to males of all the heterospecific species equally, following exposure to false olfactory cues.…”
Section: Methodsmentioning
confidence: 99%
“…In Drosophila, OR83b oligomerizes with other receptors to produce functional receptors for odorants (Elmore et al 2003;Larsson et al 2004;Neuhaus et al 2005). OR83b mutant flies are anosmic and long-lived , suggesting that odorants influence Drosophila life span as found for C. elegans .…”
Section: Age-related Impairment In Negative Geotaxis Is Associated Wimentioning
confidence: 99%
“…Insect ORNs generally express a conventional OR conferring its odorant-binding specificity together with a highly conserved non-conventional OR belonging to the OR83b sub-family of proteins (Jones et al 2005, Krieger et al 2003, Larsson et al 2004, Pitts et al 2004. Pioneering experiments in heterologous expression systems have demonstrated that heterodimeric Drosophila ORs (DORs) elicit cellular responses following odorant stimulation (Neuhaus et al 2005, Wetzel et al 2001, effectively defining their function as bona fide ORs.…”
Section: Mosquito Olfactory Transduction: a Road Map Under Constructionmentioning
confidence: 99%
“…In contrast, conventional ORs from flies and mosquitoes hardly share any significant sequence similarity outside relatively conserved ORs such as the DOR43a/OR2 sub-group (Figure 4). The similarity between the universal co-receptor DOR83b/ OR7 group is a reflection of their conserved function as chaperones involved in protein trafficking of conventional ORs and their participation in odorant detection (Benton et al 2006, Jones et al 2005, Larsson et al 2004, Neuhaus et al 2005. Interestingly, DOR43a and the mosquito OR2 homologs do not recognise the same odorants (Hallem et al 2004a,b, Storkuhl and Kettler 2001, Wetzel et al 2001.…”
Section: Odorant Receptorsmentioning
confidence: 99%
See 1 more Smart Citation